Measuring and Modelling Non-Tariff Distortions with Special Reference to Trade in Agricultural Commodities - Lloyd, Peter J.. (OECD Development Centre Working Papers, 1991)
This paper examines issues which have arisen from the growth of non-tariff measures (NTM)s as the preferred instrument of government intervention in commodities markets, especially for agricultural commodities. In order to understand the effects of NTMs and to compare them with tariffs, the paper uses the standard concepts of equivalence and non-equivalence with tariffs . It also establishes and develops a comparison between two instruments called quasi-equivalence which is particularly useful in analysing various differences between the effects of tariffs and non-tariff measures. These differences between tariffs and NTMs have several consequences which no single measure can adequately summarise. Nevertheless, the price effects of NTMs can be captured by using either effective rates of assistance (ERA) or producer subsidy equivalents (PSE)s. When the net percentage form of the PSE is calculated using world prices and allowing for as many input price changes as ...